Activity of Zn(II)-Curcumin Complex Compound as An Antibacterial Agent Against Staphylococcus Aureus and Escherichia Coli - Silalahi, Imelda Hotmarisi; Sadenta, Deby Pascalia; Ardiningsih, Puji; Widiyantoro, Ari (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Curcumin has very broad biological activities, but it has low stability. The stability of curcumin can be enhanced by forming complex compounds with metal ions, hoping to preserve its activity. This paper reports the antibacterial activity of zinc(II)-curcumin compared with curcumin alone. Zinc(II)-curcumin complexes have been prepared using ZnCl2 metal precursor in ethanol under reflux conditions with a curcumin:metal molar ratio of 2:1. The reaction, followed by thin-layer chromatography, showed that curcumin had reacted completely with zinc(II) metal ions after 4 hours reaction. The UV-vis spectra of the Zn(II)-Curcumin complex experienced a bathochromic peak shift of 5 nm. The FTIR spectra of the zinc(II)-curcumin complex indicated interactions between the ß-1,3 diketone groups of curcumin and Zn2+ metal ions, manifested by a decrease in absorption band intensity and shift in wave numbers of phenolic -OH and enolic C=O groups. Antibacterial activities of curcumin and zinc(II)-curcumin were evaluated using the disc diffusion method against E.coli and S.aureus bacteria. Curcumin and zinc(II)-curcumin exhibited a moderate antibacterial activity against the bacteria. Inhibition zone diameters against E.coli demonstrated by curcumin and zinc(II)-curcumin at a dose of 100 µg/disc are 6.05 mm  and 5.30 mm, respectively. Meanwhile, at the same dose, curcumin and zinc(II)-curcumin showed inhibition zone diameters against S. aureus in 5.39 mm and 6.09 mm, respectively. The observations demonstrate the preservation of curcumin antibacterial activities although it is introduced with zinc(II) ion.